(untitled) (Riwayat: Educational Journal of History and Humanities, 2026)
This study aims to analyze the influence of interpersonal relationship marketing (IRM) on consumer trust in horticultural commodities at Cikurubuk Market, Tasikmalaya City. The urgency of this research arises from inconsistencies between consumer expectations and actual market conditions, particularly concerning the quality of interactions between sellers and buyers, which affects fluctuations in trust. A quantitative survey approach was employed, and data were collected from 55 consumers who had made purchases within the last six months. The data were analyzed using multiple regression, supported by classical assumption tests including normality, homogeneity of variance, autocorrelation, and multicollinearity. The results indicate that power symmetry–asymmetry, valence of the relationship, intensity of interdependence, and social- or work-related orientation simultaneously have a significant influence on consumer trust. However, only valence of the relationship and social- or work-related orientation show significant partial effects, while the other two variables do not. These findings highlight that positive relational valence and social-oriented interactions are the most decisive factors in shaping consumer trust within traditional horticultural markets. The study concludes that strengthening interpersonal relationship quality should be a strategic priority for sellers seeking to enhance consumer trust.